Legacy Effects of Extreme Heat Decreased Soil Microbial Carbon Use Efficiency - Jinhua Yin; Di Wu; Emily C. Cooledge; Chao Wang; Yue Li; Jincheng Li; Qiqi Wang; Roland Bol; David R. Chadwick; Davey L. Jones (Global Change Biology, 2026)
Extreme heat events have increased markedly over recent decades globally, with potentially severe impacts on soil carbon (C) cycling. Here, we conducted a mechanistic study to assess the impact of a single 3‐day extreme heat event (30°C, 40°C, 50°C) on C cycling in an arable soil in North Wales, exploring subsequent 200‐day potential legacy effects and shifts in microbial community structure. Soils exposed to 30°C or 40°C did not change microbial carbon use efficiency (CUE) of 14 C‐glucose, while soil exposed to 50°C showed a 48% increase in 14 C‐glucose mineralisation and halved CUE (0.33 vs. 0.66) compared with undisturbed soil. The legacy effect on soil C turnover was monitored following three additional repeated additions of 14 C‐glucose, showing that microbial C metabolism slowly recovered over 6 months. The introduction of a microbial inoculum from a non‐stressed soil failed to accelerate the recovery of microbial C metabolism in 50°C heated soil. Using soil containing a pre‐labelled 14 C native SOM pool, we found extreme heat caused a substantial loss of old C during the heat event but had no lasting impact on post‐disturbance native SOM turnover. Molecular analyses revealed that the extreme heat event decreased microbial diversity, microbial network complexity and community evenness. In conclusion, our study illustrates that extreme heat events have a substantial detrimental impact on the turnover of labile 14 C‐glucose rather than native 14 C‐SOM, with their legacy effects on soil microbial C processing lasting for a long period of time.